Genetic disruption of zebrafish mab21l1 reveals a conserved role in eye development and affected pathways. Issue 8 (12th March 2021) - Seese, Sarah E.; Deml, Brett; Muheisen, Sanaa; Sorokina, Elena; Semina, Elena V.
Abstract: Background: The male‐abnormal 21 like ( MAB21L ) genes are important in human ocular development. Homozygous loss of MAB21L1 leads to corneal dystrophy in all affected individuals along with cataracts and buphthalmos in some. The molecular function and downstream pathways of MAB21L factors are largely undefined. Results: We generated the first mab21l1 zebrafish mutant carrying a putative loss‐of‐function allele, c.107delA p.(Lys36Argfs*7). At the final stages of embryonic development, homozygous mab21l1 c.107delA fish displayed enlarged anterior chambers and corneal thinning which progressed with age. Additional studies revealed increased cell death in the mutant corneas, transformation of the cornea into a skin‐like epithelium, and progressive lens degeneration with development of fibrous masses in the anterior chamber. RNA‐seq of wild‐type and mutant ocular transcriptomes revealed significant changes in expression of several genes, including irf1a and b, stat1, elf3, krt17, tlr9, and loxa associated with immunity and/or corneal function. Abnormal expression of lysyl oxidases have been previously linked with corneal thinning, fibrosis, and lens defects in mammals, suggesting a role for loxa misexpression in the progressive mab21l1 c.107delA eye phenotype. Conclusions: Zebrafish mab21l1 is essential for normal corneal development, similar to human MAB21L1 . The identified molecular changes in mab21l1 c.107delA mutants provide the first clues about possible affected pathways. Key Findings: This manuscript presents the first mab21l1 zebrafish mutant carrying a putative loss‐of‐function allele, mab21l1c.107delA. Homozygous mab21l1c.107delA fish display an ocular phenotype that overlaps with the human disease associated with recessive MAB21L1 variants. mab21l1 deficiency results in an increase in cell death in the cornea, particularly corneal epithelial cells, transformation of the cornea into a skin‐like epithelium, and progressive lens degeneration accompanied by the development of fibrous masses in the anterior chamber. RNA‐seq studies demonstrate downregulation of various factors including irf1a, irf1b, stat1, elf3, krt17 and loxa, associated with immunity and corneal function. The identified molecular changes in mab21l1c.107delA mutants provide the first clues about possible affected pathways.